A New Method for Object Detection from Binary Images - Tuncer, Turker; Avci, Engin; Coteli, Resul (Ieee, 2015)
There could be one or more objects in an image. Object detection algorithms are needed to detect these objects. Many methods have been proposed for the detection of objects. These methods are based on various feature extraction methods. In this study, a new algorithm is proposed for the detection of objects. The proposed method is object detection model based on thresholding. In this model, image is firstly converted into binary form and coordinates points of the object on the image are determined. The detected objects are determined by using these coordinate points of the object on the image are determined and the desired object is extracted.
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: Image processing; object detection; binary image; thresholding; object detection algorithms; feature extraction methods